Pengaruh Pengungkapan Good Corporate Governance terhadap Stock Return dengan Kinerja Perusahaan sebagai Variabel Mediasi pada Perusahaan LQ-45 - Felisitas Sriayu Ningsih; Adwin Surja Atmadja (Business Accounting Review, 2017)
This study conducted to examine the influence of Good Corporate Governance Disclosure toward stock return with firm performance as a mediating variable. Good corporate governance measured by using Corporate Governance Disclosure Index (CGDI), stock return measured by using cumulative abnormal return (CAR), and firm performance measured by using return on equity (ROE). It also used debt to equity ratio (DER) and firm size as control variables. The sample used in this study was LQ-45 companies listed in Indonesia Stock Exchange (IDX) which published their annual reports and financial reports consistently during 2010 until 2015. So the final sample in this study was 108 observations selected by using purposive sampling.The data analysis technique was panel data regression by using STATA. The result showed that good corporate governance had a direct significant positive relation toward stock return without mediating by the firm performance. Debt to equity ratio had significant positive affect on firm performance and significant negative affect on stock return. While firm size had a significant negative affect on firm performance and had no significant affect on stock return.